Sonography and mammogram in the diagnosis of mammary cancer developed because of the non-malignant proliferative changes - M. A. Tsesarsky; I. G. Frolova; D. G. Bukharin; N. Yu. Fomina; E. M. Slonimskaya; S. A. Velichko (Бюллетень сибирской медицины)
According to the fact, 30% of women with mammary cancer are younger than 40 years old. It is the age when the danger of this disease is the highest. The aim of the work is the identify the diagnostic effectiveness of ultrasound research method in the first level of mammary cancer developed in fibro adenoma or in cyst, together with the nonmalignant proliferative diseases of mammary. Ultrasound research appeared to be a very effective method of diagnostics of cysts and fibroadenoma together with the expressed diffuse pathology of mammary. The differentiation line of diagnostic criteries at fibroadenoma and carcinoma if defined and the diagnostic algorithm is worked out. The necessity to use sonography as the main method of examining women (younger than 50 years old) at mammary disease is discussed.